Capacity Choice of Ground Regenerative Braking Energy Absorption Equipment for Metro Vehicle - LI Yiguo; ZHAO Qin; WANG Junping; LI Jie (机车电传动)
Based on the theoretical and test data calculation, and combining the first and second phase vehicle of Ningbo line 1 operation energy consumption statistical data, the importance of reasonable choice of ground energy recovering equipment capacity to the metro operation and vehicle was evaluated, while the choice of ground regenerative energy absorption equipment capacity was verified, which provided the basis of data fine tuning.